Analisis Yuridis Peraturan Daerah Kabupaten Toraja Utara No.15 Tahun 2011 tentang Retribusi Rumah Potong Hewan - Marchelin Marchellin (ITB AAS INDONESIA, 2024)
This research examines the implementation of Slaughterhouse Retribution (RPH) in North Toraja Regency with a focus on the aspects of internal control systems in revenue collection. According to the BPK Audit Report on the Financial Statements of PEMDA Toraja Utara in 2018, Slaughterhouse Retribution is a significant contributor to Regional Original Income, generating IDR 5,593,050,800.00 with a realization percentage of 93.22%. However, it is observed that this revenue may not be optimized due to various factors under investigation. One critical aspect under scrutiny is the legal framework governing Slaughterhouse Retribution. This study primarily delves into the regional regulations serving as the legal foundation for Slaughterhouse Retribution in North Toraja. Employing a descriptive-qualitative approach, this research collects primary data through focus group discussions and interviews, while secondary data is derived from an examination of pertinent statutes and regulations. The data is subsequently processed using content analysis and comparative analysis. The study reveals a misalignment between various provisions within North Toraja Regional Regulation No. 15 of 2011, as well as inconsistencies with other laws and regulations, notably Law No. 28 of 2009 concerning Regional Taxes and Regional Levies, and legal regulations pertaining to protected.